How Do Developers Promote Open Source Projects? - Silva Borges, Hudson; Valente, Marco Tulio (Computer (00189162), 2019)
Open source projects are increasingly important in modern software development. These projects should make use of promotion channels to communicate and establish contact with users and contributors. In this article, we describe the channels used to promote a set of 100 popular GitHub projects.